(untitled) (Journal of history, 2017)
In the article were given description to the peculiarities of exposition, the importance of the jewelry and historical and cultural heritage belong mostly to the ХІХ-ХХ century and to the collections of the second half of the period of the XVIII century in the hall of the historic Ethnography of Central State Museum. Kazakh jewelries and meaning of products were identified and analyzed that used in household . There was given definition to the scope of using Kazakh products in clothing. The main features of the jewelry in society was shown, features of the nomadic traditions of Kazakh culture was presented figuratively. The importace of updated materials was included on scientific concept in 2008. In the course of writing the article was used methods as to identify historical data, to analysis systematically certain scientific data. The concept was given during the usage and feature of the exhibits in the hall. “Eternal nation” - the importance of continuity of generation were determined.